Pengaruh digital leadership, management information system, artificial intelligence personal assistance, dan employees’ cyberloafing terhadap employee performance - Mudjiono, Gadha Septio; Fatoni, Fandi (Universitas Negeri Surabaya, 2024)
This research discusses employee performance at PT X and analyses the influence of digital leadership, management information systems, artificial intelligence personal assistance, and employees' cyberloafing. The object of this research is the employees of PT X in Surabaya, and the data collection technique used in this research is saturated samples. This study's total number of respondents was 30 people distributing questionnaires directly. This research is included in the quantitative research using data analysis techniques in the form of Structural Equation Modeling on SmartPLS version 4.0.9.6. The research results obtained are that digital leadership has a significant positive effect on employee performance, management information system has a significant positive effect on employee performance, artificial intelligence personal assistance has a significant positive impact on employee performance, and meanwhile, employees' cyberloafing has a significant negative impact on employee performance. Furthermore, the relationship between digital leadership, management information systems, artificial intelligence personal assistance, and employees' cyberloafing has a positive influence on employee performance. This research can be a reference for company leaders in improving employee performance by implementing digital leadership, management information systems, artificial intelligence personal assistance, and employees' cyberloafing for employees of PT X